Prevalence of Cardiovascular Diseases in District Buner Pakistan - Bibi, Aisha; Saeed, Kausar; Ali, Ikram; Ali, Ibrar; Khan, Mohsin; Ahmad, Naseer; Khan, Kashif; Ali Khan, Imad (Indus Journal of Bioscience Research, 2024)
Background: Cardiovascular disease (CVD) is a general term that describes a disease of heart and blood vessels. It includes four main types of diseases which are coronary heart disease, stroke, peripheral arterial disease, and aortic disease. Objective: This study aimed to assess the prevalence of cardiovascular diseases in district Buner. and to make the people aware of the cardiovascular diseases. Methods: This study was conducted with the objective of exploring the prevalence of CVDs in district Buner, KP, Pakistan from September 2022 to September 2023. A total of 850 patients’ data were recorded from different hospitals inhibiting in district Buner through specifically designed questionnaire with the help of already available literature on the topic. These medical centers were frequently visited with proper consent from the physicians. Data was collected randomly on weekly basis from each and every medical center. Results: Results revealed that among CVDs, the most prominent disease was myocardial infarction (MI) affecting 36% of patients, followed by acute coronary syndrome (ACS) affecting 25.65% of patients, ischemic heart disease (IHD) affecting 7.40% patients, angina affecting 6.70% patients, atrial fibrillation (AF) affecting 5.90% patients, left ventricular failure (LVF) affecting 5.65% patients, coronary artery disease (CAD) affecting 5.55% patients, supraventricular tachycardia (SVT) affecting 5.05% patients, and cardiomyopathy (CMP) affecting 2.10% patients. Conclusion: This study also reported that patients with CVDs represent 58% male whereas the remaining 42% were female. Most of the people affected by CVDs were having age 61-70 years accounting for 494 (58.15%) patients. The most affected Tehsil was Daggar, with 270 (31.80%) patients, and the rarest cases were reported in Tehsil Khudokhail, with 19 (2.23%) patients. The ultimate reason for this prevalence of CVDs may be due todiabetes mellitus, high blood pressure, obesity, high cholesterol level, and sedentary life style